Notas sobre a murcha bacteriana da batatinha e do tomateiro: Bacterium solanacearum E. F. Smith - de Alencar, José; Drummond, O A (Revista Ceres, 1944)
The authors present some data colleted about the brown rot disease of potatoes and tomatoes, in the State of Minas Gerais, Brasil. The disease is recognised as a serious one causing total losses in potatoes, when raised in light soil during rainy season. In dry season and also in wet and heavy soil, the disease is limited to 1 to 10% of total number of plants. Several isolations were performed to identily the organism responsible for the disease. All of them, but one, gave a Bacterium with the following characteristics : sise 0,5 x 1,9 micra, motile by one polar cilium, negative Gram, bi-polar coloration; gelatine not liquefied; colonies in agar are small, circular, smooth, convex, opalescent becoming later brown in color; it forms pellicle in broth; it alcalinises the milk; it clarifies the milk with formation of amonea and no precipi- tation of casein; nitrates reduced to nitrites; no indol forma- tion; no fermentation of carbon hydrates (dextrine, sacarose, lactose, maltose, glycose, galactose, levulose, xilose, manitol and salicine); starch not hydrolised; black pigment developed on potato stab; weak development in Cohn solution; optimum temperature 31-33¢C., fatal temp. 52°.25 C. Pathogeni- city quickly lost in culture; poor growth in agar-peptone, good one in potato-agar-peptone and in milk, in which medium the organism may be long preserved. The characteristics are the same given by E. F. Smith to his Bacterium solanacearum. One isolation, obtained from material from different source, in the same State, gave the same characteristics as the others but it didn’t clarify te milk and didn’t form amonea and also gave strong acidification of milk. These characteristics are similar to those of Baclerium solanacearum, var. asiaticum E. F. Smith. However, the authors were unable to obtain more diseased plants to conlirm this supposition with new isolations. The problem will be worked out this year, with material to be collected in the same farm where the first diseased plants came from. All the cultures were worked from mono-celled isolations (dilution method). To control the disease, the authors emphasise the importance of the inspection of seed potato plots, the use of tubers well sprouted, since the well infected ones rotted by themselves, the crop-rotation, the control of soil humidity and when the cropis attacked, it must be picked up sooner than the usual and disposed of quickly. Artificial inoculations were made in the foMowing varieties of tomato, with 100% positive resultes : Riverside, Glovel, Ponderosa, Marglobe, Pritchard, Beauty, Illinois Pride, Orange, Perfeicao, Prariana, Pan-Ame- rica, Perdrigeon, Early Baltimore, Marzano, Ficarazzi, New Stone, Essar, Extra garly Prolific, Japonez: The potato varieties Eingenheimer, Katahdin, Catiara, Ar- gentina, Bentje gave the same results. Inoculations at the base of young shoots of potatoes developed in beds for virus indexing tubers, by punctures, gave the most sensible method to test the pathogenicity of the cultures. Inoculations in banana and tobacco plants gave always negative results.